Perspektif Masyarakat terhadap Fenomena Balita yang Ditinggal Bekerja : Studi Kasus di Dusun Nganyang RT 04 dalam Tinjauan Nilai-Nilai Islam - Hilalludin Hilalludin; Dwi Winarni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the phenomenon of toddlers being left behind by parents who work in Dusun Nganyang RT 04, Sitimulyo Village, Piyungan, Bantul, and to analyze the community's perspective on this phenomenon from an Islamic viewpoint. The research uses a qualitative approach with a descriptive type of study, which presents the phenomenon in depth without using statistical tools. Data were collected through interviews, non-participant direct observation, and documentation, involving four housewives as informants. The findings show that the community views this phenomenon as an economic necessity, although there is concern about its impact on the emotional and social development of toddlers. From an Islamic perspective, parenting, especially in early childhood, is a significant responsibility of parents, emphasizing the balance between work and providing full attention to children. The implications of this study highlight the importance of religious and social education for the community to understand Islamic values related to child-rearing, as well as the need for policies that support family welfare without sacrificing children's development.